Validation of a Newly Developed Competency Assessment Tool for the Posterior Sagittal Anorectoplasty - Joosten, Maja; Bökkerink, Guus M.J.; Sutcliffe, Jonathan; Levitt, Marc A.; Diefenbach, Karen; Reck, Carlos A.; Krois, Wilfried; Blaauw, Ivo de; Botden, Sanne M.B.I. (European Journal of Pediatric Surgery, 2021)
Introduction The correction of an anorectal malformation (ARM) is complex and relatively infrequent. Simulation training and subsequent assessment may result in better clinical outcomes. Assessment can be done using a competency assessment tool (CAT). This study aims to develop and validate a CAT for the posterior sagittal anorectoplasty (PSARP) on a simulation model.Materials and Methods The CAT-PSARP was developed after consultation with experts in the field. The PSARP was divided into five steps, while tissue and instrument handling were scored separately. Participants of pediatric colorectal hands-on courses in 2019 and 2020 were asked to participate. They performed one PSARP procedure on an ARM simulation model, while being assessed by two objective observers using the CAT-PSARP.Results A total of 82 participants were enrolled. A fair interobserver agreement was found for general skills (intraclass correlation coefficient [ICC] = 0.524, p < 0.001), a good agreement for specific skills (ICC = 0.646, p < 0.001), and overall performance (ICC = 0.669, p < 0.001). The experienced group scored higher on all steps (p < 0.001), except for “anoplasty (p = 0.540),” compared with an inexperienced group.Conclusion The CAT-PSARP is a suitable objective assessment tool for the overall performance of the included steps of the PSARP for repair of an ARM on a simulation model.
Keywords: assessment; pediatric surgery; posterior sagittal anoplasty; simulation model; training